Low cost animal drawn implements for better utilization of Vertisols in the Ethiopian highlands - Astatke, A.; Mohamed-Saleem, M.A. (IBSRAM, 1992)
Discusses low cost animal drawn implements developed by the Vertisol team in Ethiopia for land shaping, planting, weeding, minimum tillage and for constructing water reservoirs in resource poor farming situations.